Ocrelizumab in Multiple Sclerosis: A Real-World Study From Spain - Sempere, Angel P.; Berenguer-Ruiz, Leticia; Borrego-Soriano, Ines; Burgos-San Jose, Amparo; Concepcion-Aramendia, Luis; Volar, Lucian; Aragones, Miguel; Palazón-Bru, Antonio (Frontiers in Neurology, 2021)
Objectives: The aim of this study was to describe the effectiveness and safety of ocrelizumab for primary progressive multiple sclerosis (PPMS) and relapsing multiple sclerosis (RMS) in a clinical practice setting. Methods: In this retrospective observational study, we analyzed clinical and MRI data in all patients with PPMS and RMS who had received at least one infusion of ocrelizumab in two health areas in south-eastern Spain. Patients involved in any ocrelizumab trial and those patients with a follow-up shorter than 6 months were excluded. Results: The cohort included 70 patients (42 women) who had received ocrelizumab; 30% had PPMS and 70%, RMS. At baseline, patients’ mean age was 47.1 years in the PPMS group and 39.2 years in the RMS group, while the median EDSS was 3.0 and 2.5, respectively. Median follow-up was 13.6 months. The median number of treatment cycles was 3. Most patients remained free from clinical and MRI activity after ocrelizumab initiation. Baseline MRI showed T1 Gd-enhancing lesions in 57% of the patients; by the first MRI control at 4-6 months, all patients except one were free of T1 Gd-enhancing lesions (69/70, 98.6% P<0.001). The proportion of patients with NEDA was 94% in the group of RMS patients who were followed for at least one year. Ocrelizumab was generally well tolerated; the most common adverse events were infusion-related reactions and infections, none of which were serious. Conclusions: Our real-world study supports the tolerability, safety, and effectiveness of ocrelizumab in clinical practice.